Serum thymosin α 1 levels in patients with chronic inflammatory autoimmune diseases. (1st August 2016) - Pica, F.; Chimenti, M. S.; Gaziano, R.; Buè, C.; Casalinuovo, I. A.; Triggianese, P.; Conigliaro, P.; Di Carlo, D.; Cordero, V.; Adorno, G.; Volpi, A.; Perricone, R.; et al.
Summary: Thymosin alpha 1 (Tα1) is a powerful modulator of immunity and inflammation. Despite years of studies, there are a few reports evaluating serum Tα1 in health and disease. We studied a cohort of healthy individuals in comparison with patients affected by chronic inflammatory autoimmune diseases. Sera from 120 blood donors (healthy controls, HC), 120 patients with psoriatic arthritis (PsA), 40 with rheumatoid arthritis (RA) and 40 with systemic lupus erythematosus (SLE), attending the Transfusion Medicine or the Rheumatology Clinic at the Policlinico Tor Vergata, Rome, Italy, were tested for Tα1 content by means of a commercial enzyme‐linked immunosorbent assay (ELISA) kit. Data were analysed in relation to demographic and clinical characteristics of patients and controls. A gender difference was found in the HC group, where females had lower serum Tα1 levels than males ( P < 0·0001). Patients had lower serum Tα1 levels than HC ( P < 0·0001), the lowest were observed in PsA group ( P < 0·0001 versus all the other groups). Among all patients, those who at the time of blood collection were taking disease‐modifying anti‐rheumatic drugs (DMARD) plus steroids had significantly higher Tα1 levels than those taking DMARD alone ( P = 0·044) or no treatment ( P < 0·0001), but not of those taking steroids alone ( P = 0·280). However, whichever type of treatment was taken by the patients, serum Tα1 was still significantly lower than in HC and there was no treatment‐related difference in PsA group. Further prospective studies are necessary to confirm and deepen these observations. They might improve our understanding on the regulatory role of Tα1 in health and disease and increase our knowledge of the pathogenesis of chronic inflammatory autoimmune diseases.